Visible Light Positioning Based on Architecture Information: Method and Performance - Soto-Gomez, J; Seguel-Gonzalez, F (Institution of Engineering and Technology, 2019)
In this paper a novel 2-D range free positioning method which uses visible light communications network architecture is presented. The algorithm performance for lattice and hexagonal LED lighting infrastructure deployment is obtained by computational simulation. The robustness of our method against changes on receiver s field of view and mismatch between the assumed vertical distance and real vertical position is simulated in a room of dimensions 5 × 5 × 2.5 m. A localization interest zone with receiver s height between 0.5 and 1.1 m measured from the floor is considered as variation on vertical distance. Moreover, FOV s ranging from 90° to 130° are used to measure the behaviour of the method when different built-in photo detectors are incorporated in the mobile device. Our algorithm overcomes three traditional localization methods, i.e., convex position estimation, centroid and received signal strength based trilateration when changes in the FOV occurs. In addition to this, it shows better accuracy than other range free algorithms when an assumed height difference mismatch of up to 30 cm exist. The method shows better coverage than range based methods being able to reduce border effects and perform localization with reliable accuracy using only one connected cell and a single photo detector. © The Institution of Engineering and Technology 2019.